PROMOTING HUMANISTIC TEACHING THROUGH SPEECH ACTS AWARENESS - Andri Donal (Universitas Negeri Padang, 2015)
Education is verv important because it is a moral enterprise that shapes human development. A good education system should be able to develop students' potential by appreciating the diversity owned by students without pressure. force and violence especially from the individual of a teacher. In the cbntext of classroom developing autonomy and humanity is not a natural process, but an interactive process between teacher and students under social power relationships. Teacher's speech acts in the classroom potentially break the humanistic education principles. Discussing the relationship betrveen teacher's speech acts and the humanistic teaching is interesting to be explored. A teacher. someone who has authority in the classroom should be able to implement the humanistic teaching. Humanistic teaching is a teaching process that considers the principles of humanism involving the consideration of each individual's potential and self actualization. Because in teaching learning process: the interaction between teacher and students occurs naturally. It needs teacher's awareness in uttering speech acts. Teachers must be aware that their speech acts will have great impact to students. It can shape students' attitude not only towards teacher but also to lesson taught by that teacher. Therefore, promoting the implementation of humanistic teaching through teachers' speech acts awareness is a must.